Mealworms And Crickets As Protein Sources In Complete Rations Formulated With Kenaf, Yeast And Cereal Grains For Ruminants In Malaysia - Yusoff, Husna Fasihah Mohd (2024)
Mealworm (Tenebrio molitor) and field cricket (Gryllus assimilis) as a protein source were evaluated for the production of high quality ruminant feed in Malaysia. Nutrient evaluations were also conducted on fibre source, namely kenaf. Whereas molasses, corn and wheat grains were energy sources. Nutrients evaluation in ruminant feed production should not only focused on protein alone but also included metabolizable energy, crude fibre and crude lipid. The feedstuff evaluated in this study suggested that they are potentially high in protein and energy. Both mealworms and crickets were found to contain high amounts of protein, while corn and wheat contained high energy with moderate crude protein contents. While kenaf showed high potential as fibre source for ruminants. This study also evaluated the use of dried malt extract, molasses and sugar in substrates fermentation for yeast production. In this study, multiple energy sources were utilised which contributed to the lowering of feed costs while enhancing the feed formulation. The novelty in this research was the insects used to replace soybean meal as a protein source in ruminant feed formulation. Insects have been widely included as a protein source in poultry industry. However, information on the use of insects as protein source in the ruminants is still limited. Hence, in order to determine the nutritional value of feed ingredients, several feed analysis were also carried out in each ingredients. Proximate analysis on feed ingredients were conducted and reported in chapters 3 to 7.